2021
DOI: 10.3389/pore.2021.1610075
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Metabolism Scoring Predicts Prognosis and Therapeutic Resistance in Hepatocellular Carcinoma

Abstract: Glutamine metabolism (GM) plays a critical role in hepatocellular carcinoma (HCC); however, a comprehensive methodology to quantify GM activity is still lacking. We developed a transcriptome-based GMScore to evaluate GM activity and investigated the association of GMScore with prognosis and therapeutic resistance. Two independent HCC cohorts with transcriptome data were selected from The Cancer Genome Atlas (TCGA, n = 365) and the International Cancer Genome Consortium (ICGC, n = 231). The expression of 41 GM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Recently, Ying et al [12] suggested a multigene model related to GM could predict prognosis and therapeutic resistance in hepatocellular carcinoma. A risk model based on GMScore exhibited superior than other biomarkers for prognostic prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ying et al [12] suggested a multigene model related to GM could predict prognosis and therapeutic resistance in hepatocellular carcinoma. A risk model based on GMScore exhibited superior than other biomarkers for prognostic prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine metabolism-related genes (names as GMRGs) were extracted from the Gene Ontology (GO) initiative and published literatures [11,12]. The 3 level of RNA-seq data and clinical characteristics of LUAD were obtained from TCGA website (https://portal.gdc.cancer.gov/).…”
Section: Data Collectionmentioning
confidence: 99%
“…High GS expression appears to be associated with poor prognosis in HCC, but this conclusion is controversial. [17][18][19][20] It has been reported that GS positive (GS+) HCC tumors have a higher differentiation grade [17] and that patients with GS+ HCC tumors experience better overall survival (OS) after radiofrequency thermal ablation. [18] In contrast, reports from other groups have shown that GS may enhance metastasis and recurrence in HCC, [19] and patients with higher GS expression have worse OS when receiving postoperative adjuvant transcatheter arterial chemoembolization.…”
Section: Introductionmentioning
confidence: 99%
“…Immunostaining of both GS and Arg1 is widely used in clinical pathology to discriminate HCC from intrahepatic cholangiocarcinoma, though the role of GS and Arg1 immunostaining in the molecular classification of HCC is still undefined. High GS expression appears to be associated with poor prognosis in HCC, but this conclusion is controversial [17–20] . It has been reported that GS positive (GS+) HCC tumors have a higher differentiation grade [17] and that patients with GS+ HCC tumors experience better overall survival (OS) after radiofrequency thermal ablation [18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation